Influence of soil properties on Ni accumulation in food crops and corresponding dietary health risk with a typical Chinese diet. (6th October 2017) - Luo, D.; Zheng, H.; Chen, Y.; Deleporte, P.; Xie, T.; Staunton, S.; Wang, G.
Abstract: Nickel (Ni), an essential micronutrient, is toxic to plants and animals at elevated levels. Fewer data are available on the dynamics of Ni than for trace metals such as Cu and Zn. Dietary intake is the major source of Ni, but almost no information is available on dietary intake for Asian populations whose diet contains much less animal products and processed foods than in Western countries. In south‐eastern China, most food is grown on peri‐urban agricultural land and thus, food crops from these areas should be the major source of dietary Ni. A large‐scale survey of Ni in soils and edible crops, including 515 sites and 24 crop species from 10 crop groups, was conducted in Fujian Province, SE China, to assess Ni intake for a typical SE Asian diet. Correlation, principal component analysis (PCA) and data mining were used to identify soil and plant factors that determine Ni accumulation in crops. Both soil Ni content and plant species contributed to Ni accumulation. Crop Ni (Nicrop ) was positively correlated with soil Ni DTPA‐extractible (diethylenetriaminepentaacetic acid) (NiDTPA ) for many crops. PCA did not identify strong relations between soil‐to‐crop transfer factors and any soil properties. Stepwise linear correlations found positive correlations between Nicrop and NiDTPA ; however, relationships between Nicrop and both silt content and pH varied between crops. Dietary intake of foods containing mean Ni content could lead to health risks, especially for children. It was concluded that sandy soils, rich in organic matter with a large Ni content, are unsuitable for the production of rice and legumes.